Glucagon-like peptide-1 and glucose-dependent insulinotropic polypeptide agonists for the treatment of obesity and diabetes mellitus - Alexander C. Martins; Beatriz G. de la Torre; Fernando Albericio (Exploration of Drug Science)
Pharmaceutical interventions play a vital role in managing various conditions, including weight-related issues such as obesity. In this context, lifestyle changes are often challenging to maintain, especially for individuals struggling with this condition. Obesity is strongly linked to serious health conditions like cardiovascular disease and insulin resistance, leading to a cascade of health risks. Importantly, the development of effective and safe weight loss medications has been challenging. Diabetes mellitus (DM), the incidence of which is also rising, is closely related to obesity. The annual rate of DM cases has increased significantly, mirroring trends in obesity. Pharmaceutical companies have made significant progress in developing drugs that address both diabetes and obesity. Glucagon-like peptide-1 receptor agonists (GLP-1RAs) have emerged as a promising class of medications with dual benefits in managing diabetes and aiding weight loss such as semaglutide, liraglutide, dulaglutide, exenatide, among others. However, despite their effectiveness, they can be expensive. The availability of various GLP-1RAs offers flexibility in diabetes management, but the surge in their prescription has led to a global shortage. Health authorities are working to address this issue, while pharmaceutical companies are exploring new paths to improve the quality of these drugs. In this context, tirzepatide stands out as a medication targeting key hormones involved in obesity and DM. Another potential breakthrough, retatrutide, is also being developed for these two conditions, but it requires further research. In this paper, the authors address all the GLP-1RA options developed to date, covering their mechanisms of action, efficacy, and chemical structures, among other aspects.